KEMANDIRIAN ANAK USIA DINI DENGAN STATUS ORANG TUA YANG BEKERJA - Syarifatul Margina, - (2020)
The basis for building a generation is early childhood. At this stage, early childhood will experience a stage of psychosocial development, which means that children will learn to believe in themselves so that they can develop their independence. Early childhood independence is the ability to carry out tasks in accordance with their development and capacity, as well as being able to be responsible for everything they do. The process of cultivating independence begins with family at home, then joins a social environment that can encourage children to make skills so that children carry out activities in a pleasant atmosphere. The phenomenon that occurs in the present era is that many parents work to make ends meet. Even a mother is involved in helping her husband to earn additional income for the family. Judging from the data from the Bandung City Statistics Center, it is recorded that there are 398,941 working women. As the workforce increases from year to year it is caused by economic factors in the family that make women work. In addition, more and more women who are not in the workforce (schools and households) are joining the labor force to work. Therefore, working mothers have less time to spend with their children, in that situation child care is done by substitute caregivers, this will make children learn to be independent. Working mothers must be able to work together with their husbands and even their families to divide the duties of caring for children. Therefore, this study analyzes the independence of early childhood with the status of working parents. The results of this study indicate that with the status of working parents, parents have a strategy in providing care and instilling independence in their children.